Developing an Improvised Secured Routing Protocol for WSNS Using Hierarchical & Clustered Approach - Pranav Pradip Chippalkatti, Swagat Madhav Karve, Rajesh Maharudra Patil, Nagaraja (Mathematical Statistician and Engineering Applications, 2021)
This paper is related to the developing of an improvised secured routing protocol for WSNs using hierarchical & clustered approach. NS2 is used as the simulation tool to simulate the outputs. The simulation results shows the effectivity of the methodology that is being proposed by us.